1998
DOI: 10.1557/s1092578300000880
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of phase separation in InGaN due to elastic strain

Abstract: The effect of elastic strain in epitaxial InGaN layers coherently grown on GaN wafers on spinodal decomposition of the ternary compound is examined. The effect results in considerable suppression of phase separation in the strained InGaN layers. To predict correctly the position of the miscibility gap in the T-x diagram it is important to take into account the compositional dependence of the elastic constants of the ternary compound. The contribution of the elastic strain to the Gibbs free energy of InGaN is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(101 citation statements)
references
References 16 publications
7
91
0
3
Order By: Relevance
“…Early theoretical calculations predicted that compositional inhomogeneities in InGaN are a natural consequence of microscopic-strain-induced immiscibility of InN and GaN materials [29], and hence increase in severity as the In content increases from zero towards that necessary for deep green emission (and presumably continuing to increase in severity as the 50:50 alloy is approached). However, the applicability of these conclusions to thin, fully strained InGaN QWs grown on GaN has been challenged [37].…”
Section: Compositional Inhomogeneitiesmentioning
confidence: 99%
“…Early theoretical calculations predicted that compositional inhomogeneities in InGaN are a natural consequence of microscopic-strain-induced immiscibility of InN and GaN materials [29], and hence increase in severity as the In content increases from zero towards that necessary for deep green emission (and presumably continuing to increase in severity as the 50:50 alloy is approached). However, the applicability of these conclusions to thin, fully strained InGaN QWs grown on GaN has been challenged [37].…”
Section: Compositional Inhomogeneitiesmentioning
confidence: 99%
“…18 In addition, more sophisticated thermodynamic calculations, which took into account the fact that the InGaN quantum wells were strained, suggested that the strain should suppress the decomposition and that InGaN should be a homogeneous random alloy up to an indium content of at least 40%. 19 Hence, the bright light emission from InGaN cannot be due to the formation of indium-rich clusters. So the puzzle remained: Why do InGaN quantum wells emit brilliant light when the dislocation density is so high?…”
Section: Why Do Highly Defective Gan-based Materials Emit Brilliant Lmentioning
confidence: 99%
“…However Karpov [32] has calculated the phase diagram for an InGaN layer epitaxially matched to a GaN layer, which puts the InGaN into biaxial compression. The effect of the strain is to stabilise the InGaN, and no decomposition is predicted for normal growth conditions.…”
Section: Thermodynamics Of Strained Inganmentioning
confidence: 99%